PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN ALAM MATERI PERPINDAHAN KALOR MELALUI MEDIA QUIZIZZ PADA SISWA KELAS V SEKOLAH DASAR - Indah Safitri (Universitas Muria Kudus, 2022)
This study aims to describe the Quizizz media as a learning evaluation application and improve learning evaluation results. This classroom action research was conducted in three cycles with one learning meeting in each cycle. Each cycle consists of planning, implementation, observation, and reflection. Every meeting, students work on learning evaluations through quizzz. The research subjects were 15 students of class V SD 3 Karangampel Kaliwungu Kudus. The results showed that Quizizz is a learning media for learning evaluation activities that make students feel motivated to do evaluations. Learning outcomes are shown from the increase in Quizizz results. In the first cycle, the number of students who completed was 47%. The results increased in the second cycle to 73% and in the third cycle the students' completeness reached 87%. Students are more motivated to be able to do quizzz so that learning outcomes increase.